What Might Happen to School Mathematics in 2013? - Lee Peng Yee (SEAMEO Regional Centre for QITEP in Mathematics, 2011)
The following commentary on the direction and substance of the curriculum reviewprocess currently happening in Singapore was included because of its interest toreaders from other countries. However, the views expressed here are those of theauthor, a respected and experienced Asian mathematics educator, and do notnecessarily reflect those of the editors or the international advisory panel.